The Mindset Cultivation of Knowledge with Virtue for Bachelor’s Degree Students by Using the Philosophy of Sufficiency Economy - Yurarach, Subin (An Online Journal of Education, 2021)
Three main objectives of this research were (1) to study the level of the use of Philosophy of Sufficiency Economy (PSE) for living, (2) to analyze the variables effecting on the use of PSE for living, and (3) to propose the guidelines of the mindset cultivation of “Knowledge with Virtue” by using PSE. For quantitative analysis (QUAN), the sample consisted of the 390 bachelor’s degree students. For qualitative analysis (qual), the sample consisted of six key informants. Three types of research instruments were included: a questionnaire, an in-depth interview form, and a field note. The research findings were as follows: (1) PSE was used by the students at high level by applying the principles of Moderation, Reasonableness, and Self-Immunity to their study and living, (2) intention directly effects on the use of PSE for living, behavioral perception directly effects on the intention and on attitude towards the use of PSE for living, the behavioral perception indirectly effects on the use of PSE for living, and (3) the guidelines of mindset cultivation of knowledge with virtue were five steps comprising Step 1: Incubation, Step 2: Perception, Step 3: Exercise, Step 4: Lesson Learned, and Step 5: Construction of Knowledge and Thinking Bodies by carrying out through the teaching and learning process in which the Philosophy of Sufficiency Economy is applied.